(untitled) (American Journal of Interdisciplinary Research and Development, 2026)
Harmonic hearing is the ability to perceive, anticipate, and mentally organize simultaneous and successive sonorities as meaningful structures—chords, functions, cadences, and progressions—rather than as isolated “vertical stacks.” This article explains how harmonic hearing develops from basic acoustic and perceptual sensitivities to higher-level musical understanding and expressive use.